A liberdade e a felicidade do indivíduo na racionalidade do trabalho no capitalismo tardio: a (im)possibilidade administrada - Chaves, Juliana de Castro (2007)
This paper is based on a theoretical research aiming to analyze the possibility of freedom and happiness in the rationality of work in late capitalism. The foundation of this study is the Critical Theory of Society, connected to the School of Frankfurt and represented by Max Horkheimer, Theodor Adorno and Herbert Marcuse, in dialog, discussion, and confront with other theoretical references in order to deepen the debate. To the authors of the Critical Theory, freedom and happiness can only be conceived in the attachment of the individual to society. Thus, this thesis brings to the discussion the contributions of Marx and Freud, authors that take into consideration this relationship and indicate that work must be questioned as a category fundamental for the formation of man, because it produces Ego suffering, domination, and fragility. The foundations to analyze freedom and happiness in the present are developed based on discussions about the concepts of these two dimensions in differentiated organizations, and their articulations with the rationality of work. After that, it is discussed the configuration of rationality of work in contemporary society, which is spread over several social spheres, determining educational modes and leisure time. This rationality is contradictory, because it emphasizes the formation of a worker-citizen possessing competences that enhance the individuality and the potential to be autonomous and free in order to search for welfare and happiness, although presenting an overwhelming heteronomy. Concomitantly with the emancipation enhancement, apathy, fortuitous happiness, sacrifice, fear and lack of pleasure are installed in the individual. Semiformation, amplified by the cultural industry, causes the individual to become fragile, thus making him receptive and functionally a reproducer of work rationality, which presents more acute subjective contradictions, although they are not reflected. The combination of objective and subjective conditions favors the formation of a massive, instrumental, and reified subjectivity that does not offer resistance to the established order and is also object of agreement, propagation, and concretization of new mechanisms of subjection. The resistance involves the analysis of this formation in the core of the objective conditions that determined it, the recognition of what makes difficult the realization of freedom and happiness, and the preparation of the individual for reflection